2014
DOI: 10.1128/jcm.03309-13
|View full text |Cite
|
Sign up to set email alerts
|

Trichosporon mycotoxinivorans Infection in Patients with Cystic Fibrosis

Abstract: We describe the clinical course of four patients who had Trichosporon mycotoxinivorans recovered from multiple sputum cultures over time with various clinical consequences but no fatalities. We also report successful rapid identification of this organism using matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry. CASE REPORTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…with severe exacerbations in CF patients [5]. On the other hand, the results of the most recent study by Shah et al showed that the isolation of T. mycotoxinivorans from CF patients is not necessarily associated with significant changes in clinical status [6]. Here we report on a CF patient with repeated isolation of T. mycotoxinivorans in respiratory specimens during the past 9 years.…”
Section: Introductionmentioning
confidence: 74%
“…with severe exacerbations in CF patients [5]. On the other hand, the results of the most recent study by Shah et al showed that the isolation of T. mycotoxinivorans from CF patients is not necessarily associated with significant changes in clinical status [6]. Here we report on a CF patient with repeated isolation of T. mycotoxinivorans in respiratory specimens during the past 9 years.…”
Section: Introductionmentioning
confidence: 74%
“…Moreover, this microorganism has been related to deep-seated infections in immunocompromised patients with invasive disposals in India (17). The use of Bruker's MALDI-TOF MS as a reliable tool for A. mycotoxinivorans species identification has helped strengthen the epidemiologic link of T. mycotoxinivorans to cystic fibrosis (18,19). Thus, it appears that inclusion of the species in the database used for clinical diagnosis is now mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Trichosporon mycotoxinivorans has been described as a chronic colonizer of the CF airways, but also as a highly pathogenic yeast in a couple of cases [27][28][29][30]. Until now, it is not clearly understood which factors trigger the variable effects of this yeast species on the CF lung.…”
Section: Epidemiology Of Fungal Colonization Of the Airways In Cf Patmentioning
confidence: 99%